Life and Death in Andersen's "Grandmother": A Systemic Functional Grammar Analysis - Dwijatmoko, Benedictus Bherman (Jurnal KATA, 2019)
Hans Christian Andersen's "Grandmother" is a well-written short story about life and death. The analysis of the story using Systemic Functional Grammar (SFG) reveals the meaning and ideology which the writer expresses through the work. In the ideational metafunction, the story uses the material and relational processes the most. The use of the two processes presents the grandmother and her character vividly and clearly. In the interpersonal metafunction, the sentences mostly use grandmother, she, and other objects related to her as the subject. The use shows how meaningful the grandmother to her granddaugher, the narrator, is. Furthermore, the change of the tense also indicates the significant transformation of the grandmother. Finally, in the textual metafunction, though low, the use of marked themes emphasizes the life phases of the grandmother. The analysis of the text using SFG reveals the centrality of life and death in the story. The analysis of the ideational, interpersonal, and textual metafunctions of the text reveals well the meaning and ideology which the story conveys. Death is only a transform of a life to another life.